A stable aminyl radical metal complex. - Büttner, T; Geier, J; Frison, G; Harmer, J; Calle, C; Schweiger, A; Schönberg, H; Grützmacher, H (2005)
Metal-stabilized phenoxyl radicals appear to be important intermediates in a variety of enzymatic oxidations. We report that transition metal coordination also supports an aminyl radical, resulting in a stable crystalline complex: [Rh(I)(trop2N.)(bipy)]+OTf- (where trop is 5-H-dibenzo[a,d]cycloheptene-5-yl, bipy is 2,2'-bipyridyl, OTf- is trifluorosulfonate). It is accessible under mild conditions by one-electron oxidation of the amide complex [Rh(I)(trop2N)(bipy)], at a potential of -0.55 volt versus ferrocene/ferrocenium. Both electron paramagnetic resonance spectroscopy and density functional theory support 57% localization of the unpaired spin at N. In reactions with H-atom donors, the Rh-coordinated aminyl behaves as a nucleophilic radical.